A collective review of cases with cryptorchidism managed in a teaching hospital in Sudan - Alawad, Awad; Hussain, Walaa Amin; Younis, Faisal H. (International Journal of Medicine, 2015)
Background: Cryptorchidism is one of the most common urogenital abnormalities in male children. Delayed diagnosis and treatment of cryptorchidism lead to complications such as infertility, malignancy and testis torsion.Objective: To determine the cause of delayed presentation, complications recorded, the surgical treatment offered in a developing country.Methods:A retrospective review of patients’ records from December 2012 to December 2014 was carried out. Sixty one patients presented to the University Charity Teaching Hospital during this period.Results: Sixty one patients were included in the study. Age ranged from 1-75 years with mean at surgery is 11 years. Twenty seven patients (44%) presented after 24 months, 3 (4.9%) less than 12 months, and 23 (37.3%) less than 1 month. Age at operation, 7 (13%) were £ 2years, 15 (28%) were 2-5years, 39 (59%) were > 5 years.Fifty four (88.5%) patients have undergone orchidopexy, 3(4.9%) orchidectomies, 1 (1.6%) biopsy, 1 (1.6%) exploratory laparotomy, and in 2 (3.3%) cases operation wasn’t done.Conclusion:Late presentation observed in this study is alarming and action should be taken by spreading awareness in the community and ensuring adequate neonatal and children examination in order to avoid the complications.